RE-CODING DNA OF PUBLIC ADMINISTRATION Sebagai Upaya Peningkatan Public Service - Agus Wahono (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2011)
Re-coding DNA of Public Administration as Improving Public Servic, which in this study said that the overall administrative reform regarding dimensions and essentially a very broad spectrum and complex with a very clear objective of improving administrative performance of the government bureaucracy. Every government apparatus thus needs to be improved administrative skills, responsibility, moral ethics, his personality, his spirit, creativity, loyalty, passion interests with him, discipline, autonomy and mutual dependence and professionalism. And institutions need to be reminded among other structures, systems and procedures, leadership, coordination, management participation, adaptation, relationship with clients, efficiency and effectiveness, and responsibilitasnya akontabilitas. Recognizing the vast and complex area administration reform direction and the implementation needs to gain support from other sectors such as politics, economics, law and so on.